RE-KREASI MUATAN FOLKLORE PADA MOTIF BATIK KONTEMPORER DENGAN TEKNOLOGI AUGMENTED REALITY - Hartanti, Monica; Maitri, Irena Ayu (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2020)
Cultural products can form the identity of an area, one of which is Batik. Contemporary Semarang Batik is one of the cultural products of the City of Semarang that has a unique form of folklore content on its motives, which illustrates the identity of the city of Semarang. Regrettably, most of the people of Semarang city do not know the content of the folklore on their homemade Batik cloth. From an economic standpoint, this is not a problem, but when viewed in terms of the sustainability of cultural heritage, this should not happen. In the era of globalization, cultural products need to have collaborated with technology; it is necessary to re-create past art forms into something interesting for modern society to consume. The data collected in this study used a qualitative method in the form of interviews and direct observations visiting Semarang and quantitative Batik artisans by distributing questionnaires online. The process of transforming traditions, visually using Bahasa Rupa, and Augmented reality technology became the theory that underlies the re-creation of folklore in the Batik motif of Semarang. Through the collaboration of regional culture with technology has become an alternative to the re-creation of regional culture into a new form of media that is closer to the daily lives of the younger generation. This is also an effort to sustain the cultural heritage of the city of Semarang.